A grounded theory of type 2 diabetes prevention and risk perception. Issue 3 (15th January 2021) - Vaja, Ishfaq; Umeh, Kanayo F.; Abayomi, Julie C.; Patel, Tasneem; Newson, Lisa
Abstract : Objective: Type 2 diabetes (T2D) prevention programmes should target high‐risk groups. Previous research has highlighted minimal engagement in such services from South Asian (SA) people. Given SA's elevated risk of T2D, there is a need to understand their perceptions, risks, and beliefs about T2D. Design: This study aimed to assess T2D risk perception within a community sample of SA people using Grounded Theory methodology. Specifically, health beliefs were assessed, and we explored how these beliefs affected their T2D risk perceptions. Method: Twenty SA participants (mean age = 38 years) without a diagnosis of T2D were recruited from community and religious settings across the North West of England. In line with grounded theory (Strauss & Corbin, 1990, Basics of qualitative research: Grounded theory procedures and techniques. Newbury Park: Sage Publications), data collection and analysis coincided. Results: The superordinate category of Culturally Situated Risk Perception incorporated a complex psychological understanding of the formation of T2D risk perception, which takes into account the social, cultural, and community‐based environmental factors. This superordinate category was explained via two core categories (1) Diminished Responsibility, informed by sub‐categories of Destiny and Heredity, and (2) Influencing Healthy Lifestyle Behaviours, informed by sub‐categories of Socio‐cultural and Environmental. Conclusion: This study investigated risk perception of T2D within the SA community. When considering health prevention in the context of an individual's culture, we need to consider the social context in which they live. Failure to acknowledge the cultural‐situated T2D risk perception relevant to health promotion and illness messages may account for the issues identified with health care engagement in the SA population.